A Brake System Coefficient of Friction Estimation Using 3D Friction Maps - Francesco Varriale; Stefano Candeo; Gabriele Riva; Jens Wahlström; Yezhe Lyu (Lubricants, 2022)
The coefficient of friction (COF) is one of the core factors in the evaluation of brake system performance. It is challenging to predict the COF, since it is strongly influenced by several parameters such as contact pressure (p), slip rate (v) and temperature (T) that depend on the driving conditions. There is a need for better models to describe how the brake friction varies under different driving conditions. The purpose of this research is to study the possibility of using 3D friction pvT-maps to estimate the COF of a disc brake system under different driving conditions. The 3D friction pvT-maps are created by filtering results of material tests conducted in a mini-dyno inertia bench. The COF measured under different driving cycles in an inertia dyno bench with the full brake system are compared with the COF estimated by the friction maps coming from the reduced scale dyno bench to investigate the validity of the simulation approach. This study shows that mini dyno bench is suitable to obtain a tribological characterization of the friction pad–disc rotor contact pair and is able to replace the full inertia dyno bench to investigate the brake system performance.